1476 North Wales Vascular Surgery Zoom Webinar Teaching Programme for Medical Students and Junior Doctors. (12th October 2021) - Iqbal, Z; Youssef, A; Abdaldayem, A; Shaikh, F
Abstract: Aim: Surgical Education is now more widely delivered on virtual platforms due to the COVID-19 pandemic. Due to centralisation of Vascular Surgery services in North Wales to Glan Clwyd Hospital (Central), Medical Students, Junior Doctors and General Surgical Registrars have reduced exposure to the speciality and the management of common cases in neighbouring hospitals (East and West). Subsequently, we developed a regional virtual teaching programme to help bridge gaps in knowledge and to instil confidence when providing a service. Method: We developed a 4-part didactic webinar educational programme which covered parts of the medical undergraduate and MRCS curricula pertaining to Vascular Surgery. Under/Postgraduate educational leads from Central, East and West were contacted to promote our programme. Webinars were delivered on ZOOM video conferencing once weekly throughout December 2020. Feedback forms were collected on Google Forms™ and used 5-point Linkert scales to grade responses and analysis of data was carried out on Microsoft Excel®. Results: 186 feedback forms were collected and respondents reported significant improvements in knowledge in each of the subjects covered: [1] Abdominal Aortic Aneurysms - (2.59±1.07/5 to 4.23±0.65/5, p = <0.0001, n = 60), [2] Acute Limb Ischaemia – (2.55±1.11/5 to 4.21±0.72/5, p = <0.0001, n = 42); [3] Chronic Limb Ischaemia (2.57±1.03/5 to 4.23±0.77/5, p = <0.0001, n = 35); [4] Vascular Emergencies (2.94±1.28/5 to 4.37±0.63/5, p = <0.0001, n = 49). Overall topic interest, presentational skills and clinical usefulness was also rated highly. Conclusions: Through this virtually delivered regional teaching programme, we successfully enhanced Vascular Surgery knowledge and addressed the educational needs of Medical Students and Junior Doctors across North Wales.